THE CIRCLE IS STRONG : family, identity and the child welfare system - Varley, Autumn (2017)
This research paper was completed and submitted at Nipissing University, and is made freely accessible through the University of Toronto’s TSpace repository This major research paper (MRP), "The Circle is Strong : Family, Identity and the Child Welfare System", forefronts the memories of the strong Anishinaabekwe, or Indigenous women, in my family circle, most notably my grandmother, mother, aunt, and sister. My maternal grandmother, Marie Brunelle, lived through the child welfare system in the late 1940s and became part of what is known today as the "Sixties Scoop". This research highlights the legacies and the intergenerational impacts of the child welfare system in our familiy and examines our stories of resilience, healing, and reconciliation. Through the use of memory, photographs, diaries, art, novels, plays, and film, it embraces and utilizes story in all of its many forms to contribute to history that honours Anishinabeg ways of knowing. Story is the method through which we can understand our family's history : our displacement from Anishinabeg traditional territory, the strength and resilience of the women in my family, our healing through ceremony, and my journey to an understanding of self as an Anishinaabekwe.